Assessment of Pizotifen efficacy in the management of recurrent aphthus stomatitis - A double blind trial - (Mustansiria Dental Journal, 2018)
Recurrent aphthus ulceration (RAU) is one of the most common and troublesome oral lesions, as they are extremely painful and recurrent, no single preparation is uniformly effective in the treatment of this condition.A double blind cross-over trial assessed the value of pizotifen in reducing the severity of pain, duration and frequency of ulcers in a group of recurrent aphthus ulcer patients. Active & placebo preparation were used for a period of 4 weeks each; 42 patients completed the use of both preparations.20 patients out of 28 patients on pizotifen therapy experienced a decrease in the severity of pain as well as decrease in the duration of each attack, where as 18 patients in the same group reported reduction in the frequency of the disease.Pizotifen reduced pain severity, duration and frequency of oral ulcerations in the examined group